Prostate cancer in Saudi Arabia: trends in incidence, morphological and epidemiological characteristics - Alshehri, Bandar M. (International Journal of Research in Medical Sciences, 2020)
Background: Prostate cancer (PCa) is the second most common cause of cancer and the second leading cause of cancer death among men worldwide. This paper aims to determine the incidence of the prostate cancer cases in Saudi Arabia between 1994 and 2016. Methods: In this study, the statistics of prostate cancer cases recorded in reports of the Saudi cancer registry for the period from 1994 to 2016 are used. The data and numbers of these reports were assessed to review the full picture during the study period. Age-standardized and age-specific incidence rates were calculated for these purposes. Results: In total, 89,880 cancer cases were recorded for the period between 1994 and 2016. The number of prostate cancer cases out of this total is 5,332. The age-adjusted prostate cancer incidence increased from 4.1 in 1994 to 6.3 in 2016. A variation in the incidence of prostate cancer by region was noticed, and a direct relationship was identified between prostate cancer rates and the ages of those with prostate cancer, with the majority of people with prostate cancer being over 50 years. Conclusions: The overall appearance of prostate cancer is moving upwards. Differences in the incidence rates between men who live in different Saudi regions suggest that environment, behaviour and genetic factors may be a cause. Exploring these factors is necessary to take advantage of them while drawing up the prevention plans.